2013
DOI: 10.20429/ijsotl.2013.070113
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Presence in Online Courses and Student Satisfaction

Abstract: This case study explores the role of the online instructor and how they influence student satisfaction. While there has been a substantial body of literature on what impacts on student satisfaction when students study online, there is far less literature focussing on how the instructor mediates this satisfaction, in particular satisfaction related to quality of feedback and teaching. This case study addresses this gap by exploring the performance of two instructors across six fully online courses in a post gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 50 publications
4
67
0
1
Order By: Relevance
“…Dunlap & Lowenthal, (2009) stated that teaching presence is the ability of a teacher or teachers to support and enhance social and cognitive presence through instructional management, building understanding, and direct instruction. Ladyshewsky (2013) also reported that teaching presence appeared to positively influence students' satisfaction with an online course of study. Teaching presence emphasizes the teacher's role and responsibilities in their learning environment.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Dunlap & Lowenthal, (2009) stated that teaching presence is the ability of a teacher or teachers to support and enhance social and cognitive presence through instructional management, building understanding, and direct instruction. Ladyshewsky (2013) also reported that teaching presence appeared to positively influence students' satisfaction with an online course of study. Teaching presence emphasizes the teacher's role and responsibilities in their learning environment.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Instructors should start such an activity by triggering the learning process, encouraging students to reflect on it within the learning community, and making sure that they construct meaningful knowledge and start learning new knowledge (Garrison et al, 2000). According to Ladyshewsky (2013) instructors can help students to reach the last two phases by fostering their ability to challenge themselves and think critically beyond the boundaries of the problem. Encouraging learners to rate their contributions and to become aware of their level of thinking is another way to promote cognitive presence (Arbaugh et al, 2008).…”
mentioning
confidence: 99%
“…Most often, researchers will study the impact of presence on student success and satisfaction (Archibald, 2010;Allen & Laumakis, 2009;Bliss & Lawrence, 2009;Ladyshewsky, 2013;Oztok & Brett, 2011;Sheridan & Kelly, 2010;Shutt, Allen, & Laumakis, 2009;Wise, Chang, Duffy, & Del Valle, 2004). Picciano (2002) found a significant correlation between positive social presence and students' positive perception of their learning.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lang and Costello (2009) discussed factors related to the role of instructor, student attitude, social presence, usefulness, and effectiveness of ODFs. Others focused on instructor presence (e.g., see Ladyshewsky, 2013) and interaction either with instructor or with peers as well as the clarity of design (e.g., see Swan, 2001;Swan & Shih, 2005). However, very few studies have focused on the relationships between student satisfaction with using ODFs and student demographics or experience with ICT and online education (Jackson, 2014;Ryan, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%